2010
DOI: 10.1002/psc.1269
|View full text |Cite
|
Sign up to set email alerts
|

Automated ‘X‐Y’ robot for peptide synthesis with microwave heating: application to difficult peptide sequences and protein domains

Abstract: Precise microwave heating has emerged as a valuable method to aid solid-phase peptide synthesis (SPPS). New methods and reliable protocols, as well as their embodiment in automated instruments, are required to fully use this potential. Here we describe a new automated robotic instrument for SPPS with microwave heating, report protocols for its reliable use and report the application to the synthesis of long sequences, including the beta-amyloid 1-42 peptide. The instrument is built around a valve-free robot or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…35,39,44,45,47,51,61,74,76,85,87,88,138,144,145 Coupling reagents show almost identical ranking in performance at elevated temperature as at room temperature, however, the 'uronium' type coupling reagent COMU has been reported to considerably outperform the classical HBTU and HATU in the synthesis of an Aib containing pentapeptide, 61 and PyBOP, DIC, TSTU, HCTU, HBTU as well as HATU in the synthesis of the C-terminus of the MuLV CTL epitope. 45,133 Our literature survey showed that the most common coupling reagents and additives used in conventional SPPS were also those which were applied in microwave-assisted SPPS. Typically the amino acids and coupling reagents were used in 3-5 molar excess, however, for difficult sequences up to 10 molar excess has been reported ( Table 1).…”
Section: Peptide Couplingsmentioning
confidence: 99%
See 1 more Smart Citation
“…35,39,44,45,47,51,61,74,76,85,87,88,138,144,145 Coupling reagents show almost identical ranking in performance at elevated temperature as at room temperature, however, the 'uronium' type coupling reagent COMU has been reported to considerably outperform the classical HBTU and HATU in the synthesis of an Aib containing pentapeptide, 61 and PyBOP, DIC, TSTU, HCTU, HBTU as well as HATU in the synthesis of the C-terminus of the MuLV CTL epitope. 45,133 Our literature survey showed that the most common coupling reagents and additives used in conventional SPPS were also those which were applied in microwave-assisted SPPS. Typically the amino acids and coupling reagents were used in 3-5 molar excess, however, for difficult sequences up to 10 molar excess has been reported ( Table 1).…”
Section: Peptide Couplingsmentioning
confidence: 99%
“…First, b-amyloid(1-42) was successfully synthesized using microwave heating ( Table 1, entry 13 and 14). 45,46 This peptide is a current example of a long and so-called difficult 'sequence'. Secondly, the complex peptide hormone insulin, which contains two peptide chains and three disulfide bridges, has been synthesized by conventional SPPS using complex strategies.…”
Section: Peptide Couplingsmentioning
confidence: 99%
“…1,2 Historically, automated synthesis has found heavy use in the area of peptide synthesis, 3 polymer synthesis, 4 and carbohydrate synthesis. 5 Takahashi and coworkers utilized an automated synthesizer in a 36-step formal total synthesis of Taxol.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction in 1992 of MW irradiation in peptide chemistry stimulated a host of interest followed by numerous efforts to use it to overcome synthetic difficulties resulting in sluggish reactions, low yields and complex reaction crude products that were hard to purify1. During the last decade the growing interest in MW field has been marked by the progress in developing scientific MW equipment to embrace specific research needs2–5. In general, introduction of MW technology led to the shortening of reaction time that resulted in higher purity of crudes and increased yields of the pure final product.…”
Section: Scope and Commentsmentioning
confidence: 99%